Pengaruh Teknik Umpan Balik Langsung Guru dalamMeningkatkan Keterampilan Menulis Siswa Kelas 2 SMK - Agnes Aprilia; Hazairin Eko Prasetyo; Primaristuti Ika Dewi (Program Studi Pendidikan Profesi Guru, Universitas Sarjanawiyata Tamansiswa Yogyakarta, Indonesia., 2020)
The objective of this research was to describe (1) the use of direct feedback technique in improving the students’ writing skills (2) the influence of direct feedback technique in improving the students’ writing skills. This research was conducted among the second-grade students of an SMK. This study was experimental research of one group pre[1]test and post-test design. The sample of this research consisted of 32 female students. The data of this research were quantitative. The data were obtained by assessing the students’ writing through pre-test and post-test scores. The data were analyzed by using SPSS (paired sample t-test and regression). The results of the paired sample t-test showed (sig.) p 0.00 and the result of regression showed (sig.) p 0.029, it meant the hypothesis was accepted.